Downregulation of Antigen‐Presenting Cells in Tonsil and Lymph Nodes of Porcine Reproductive and Respiratory Syndrome Virus‐Infected Pigs. Issue 5 (23rd July 2012) - Rodríguez‐Gómez, I. M.; Gómez‐Laguna, J.; Barranco, I.; Pallarés, F. J.; Ramis, G.; Salguero, F. J.; Carrasco, L.
Summary: Porcine reproductive and respiratory syndrome virus (PRRSV) can persist in different organs of infected pigs, which suggests a failure in the immune response. Antigen‐presenting cells (APCs) play a pivotal role in the induction of effective T‐ and B‐cell responses. In this study, we investigated the changes in the different APC subpopulations and T‐ and B‐cell counts in the tonsil, retropharyngeal and mediastinal lymph nodes of pigs experimentally infected with a European PRRSV field isolate. Our results demonstrated that the expression of S100, SWC3, HLA‐DR molecule and CD3 was diminished in the studied organs throughout the study, observing a significant negative correlation between viral antigen and HLA‐DR expression in both retropharyngeal and mediastinal lymph nodes. In contrast, λ‐light chains showed an increase during the study. Taking all into account, after PRRSV infection, no enhancement in the number of APCs and T cells was observed, suggesting an impairment of the immune function which may allow the persistence of PRRSV into the organism.